SCIENCE, ENLIGHTENMENT AND ARCHITECTURAL ACTIVITY DURING THE PERIOD OF NADIR MUHAMMAD KHAN (World Conference on Social Sciences, Law and Public Policy, 2026)
The article studies science, enlightenment and architectural activities in the Bukhara Khanate during the reign of Ashtarkhani Nadir Muhammad Khan (1642–1645). The ruler supported scholars and poets in the palace, continued the activities of some madrasas, and also sponsored the construction of religious and educational structures - madrasas, chorbags, and a dome over the tomb of Hazrat Ali. At the same time, Nadir Muhammad Khan's attitude to science during a period of political instability and his role in the Naqshbandi order are analyzed.
Keywords: Nadir Muhammad Khan; Ashtarkhanis; Bukhara Khanate; science; enlightenment; architecture; patronage; Naqshbandi order.